Linguistic Adaptation And Socio-Religious Identity: The Expansion of Religious Vocabulary in the Ambonese Malay Language - Rumalean, Oleh Iwan (Journal of Ecohumanism, 2025)
This research examines the expansion of religious vocabulary in Ambon Malay from a socio-dialectological perspective. This research aims to understand how variations in religious vocabulary reflect the social, cultural, and religious identity of the Ambon people. Using a descriptive qualitative approach with a historical-comparative analysis method, data was collected through in-depth interviews, participatory observation, and literature documentation. The results showed that the expansion of Ambon Malay vocabulary involved phonological, morphological, and semantic adaptation processes, influenced by Arabic, Portuguese, and Dutch. Religious vocabulary variations were found to be significant in reflecting cross-religious differences, such as the use of the terms "God," "sambayang," and "sombayang." This study provides new insights into language dynamics in multicultural societies, enriching the linguistic and socio dialectological literature.